Resilience, Self-efficacy, Openness to Change, and Innovativeness of MSME Owners: A Quantitative-Qualitative Integration Before, During, and After the COVID-19 Crisis - Angeles, Imelda T. (The South East Asian Journal of Management, 2024)
Research Aims: Micro, small, and medium-sized enterprises (MSMEs) have consistently demonstrated their resilience in the face of economic challenges, particularly during crises. This study delves into how the experiences of MSMEs before, during, and after the COVID-19 crisis have translated into resilience, self-efficacy, openness to change, and innovativeness as they responded to the unprecedented challenges posed by the pandemic. Design/Methodology/Approach: This mixed-methods study combines the quantitative analysis of the characteristics of MSME owners with their narratives of their experiences during the COVID-19 crisis, translating adversity into an opportunity. Research Findings: The integrated results showed how the quantitative-qualitative insights enabled a more comprehensive understanding of the characteristics that supported resilience, resulting in maximum utilisation of technology, expansion of networks, and the creation of community enterprises. Theoretical Contribution/Originality: The integration of Psychological Capital Theory into the discussion provides a nuanced lens through which we can understand how MSMEs effectively harness their vulnerabilities to foster resilience, self-efficacy, openness to change, and innovativeness. Managerial Implications in the South East Asian Context: The findings of this study offer valuable insights for small and medium-sized enterprises in Southeast Asia seeking to develop crisis management strategies. By emphasising the pivotal characteristics of entrepreneurs, these strategies can enhance the agility and resilience of business owners in the face of adversity. Research Limitations & Implications: Future research could examine COVID-19's longitudinal and comparative effects on Southeast Asian MSMEs. These studies can help explain how small businesses adapt to and evolve to meet difficulties.